2017
DOI: 10.1111/1759-7714.12428
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic features of surgically resected pathological stage I lung adenocarcinoma harboring epidermal growth factor receptor and Kras mutation

Abstract: BackgroundThis study aimed to evaluate mutations of the epidermal growth factor receptor (EGFR) and K‐ras genes and their clinicopathological and prognostic features in patients with resected pathological stage I adenocarcinoma.MethodsWe examined 224 patients with surgically resected lung adenocarcinoma and analyzed the prognostic and predictive value of these mutations in 162 patients with pathological stage I adenocarcinoma.ResultsMutations of the EGFR and K‐ras genes were detected in 100 (44.6%) and 19 (8.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The prognosis of MIA remains unclear (60). It has been reported that EGFR mutation status has no effect on the prognosis of patients with early stage lung adenocarcinoma (61). However, the present data provide preliminary evidence to support consideration of EGFR mutation status as indication of prognostic stratification in future clinical studies involving MIA.…”
Section: Egfr Mutation Statusmentioning
confidence: 60%
“…The prognosis of MIA remains unclear (60). It has been reported that EGFR mutation status has no effect on the prognosis of patients with early stage lung adenocarcinoma (61). However, the present data provide preliminary evidence to support consideration of EGFR mutation status as indication of prognostic stratification in future clinical studies involving MIA.…”
Section: Egfr Mutation Statusmentioning
confidence: 60%
“…DFS Seventeen studies with 5,261 patients assessed the relationship between EGFR mutations and DFS, 11 , 13 , 22 , 25 , 29 , 31 , 32 , 34 38 , 42 44 , 46 , 47 and six studies demonstrated that EGFR mutations positively influenced the DFS of resected NSCLC patients. 13 , 25 , 35 , 42 , 43 , 47 Significant heterogeneity was observed between these studies ( I 2 =72%, p <0.00001; Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between EGFR mutations and OS was evaluated based on 26 studies, 11 , 13 , 16 , 19 23 , 25 , 27 31 , 33 40 , 42 44 , 47 with 8,100 patients, and seven studies 11 , 13 , 28 , 33 , 35 , 42 , 47 indicated that EGFR mutations were a favorable prognostic factor for OS in resected NSCLC patients. Some heterogeneity was noted between the studies ( I 2 =42%, p =0.008; Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that lung cancer seen in the non-smoking group is more likely to be younger than the smoker group, and that it is in the subtype of women and adenocarcinoma. KRAS mutation has been reported to be more common in the adenocarcinoma subtype [37]. Smoking specific nitric amines in cigarettes have been shown to induce KRAS gene mutations.…”
Section: Methodsmentioning
confidence: 99%